2000
DOI: 10.1007/s11745-000-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conjugated linoleic acid isomers on lipid‐metabolizing enzymes in male rats

Abstract: Male weanling Wistar rats (n = 15), weighing 200-220 g, were allocated for 6 wk to diets containing 1% (by weight) of conjugated linoleic acid (CLA), either as the 9c,11 t-isomer, the 10t,12c-isomer, or as a mixture containing 45% of each of these isomers. The five rats of the control group received 1% of oleic acid instead. Selected enzyme activities were determined in different tissues after cellular subfractionation. None of the CLA-diet induced a hepatic peroxisome-proliferation response, as evidenced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
60
0
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 51 publications
13
60
0
7
Order By: Relevance
“…For instance, the higher content of c9,t11-CLA than other CLA isomers could be a consequence of the preferential use of t10,c12-CLA for b-oxidation (Martin et al, 2000) and for synthesizing longchain metabolites from it (Evans et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the higher content of c9,t11-CLA than other CLA isomers could be a consequence of the preferential use of t10,c12-CLA for b-oxidation (Martin et al, 2000) and for synthesizing longchain metabolites from it (Evans et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction that we found in the mRNA expression of these transcriptional factors, induced by trans-10,cis-12, paralleled changes observed in ACC and FAS. Concerning the effects of CLA on liver, several studies in mice have shown that trans-10,cis-12 increased liver weight [8][9][10][11][12][13]. In some of these trials, hepatic triacylglycerol content was measured and it was concluded that hepatomegaly was due to lipid accumulation [5,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In some of these trials, hepatic triacylglycerol content was measured and it was concluded that hepatomegaly was due to lipid accumulation [5,[14][15][16]. In contrast, the studies performed on rats reported no effects on liver weight induced by CLA [4,10,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…As evidências, em roedores, de que o CLA apresentava ação hipolipidemiante, por meio da indução da β-oxidação em diversos tecidos, mas especialmente no tecido adiposo, foram surgindo de forma mais constante. Aumento da produção de corpos cetônicos, da razão β-hidroxibutirato/acetoacetato, da atividade de enzimas envolvidas na β-oxidação de ácidos graxos, como a acil CoA oxidase e a carnitinapalmitoiltransferase-1, assim como o aumento de glutationa-S-transferase, enzima afetada por proliferador de peroxissoma, contribuíram para a conclusão de que o CLA aumenta a oxidação de ácidos graxos 83,84 . O trabalho de Sergiel et al 85 foi fundamental para comprovar essa hipótese.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified
“…A diminuição, particularmente pelo isômero trans-12, cis-12 CLA, da síntese de enzimas envolvidas na lipogênese (como a lipase lipoprotéica, acetil CoA carboxilase e ácido graxo sintase), responsáveis pela clivagem dos ácidos graxos das lipoproteínas circulantes para ressíntese de triacilglicerol (LPL) e pela síntese de novo dos lípides biológicos (ACC e FAS), tem sido reportada por muitos pesquisadores 88,97 . Por outro lado, como já discutido, o aumento da β-oxidação de ácidos graxos mitocondrial e peroxissomal induzido pelo CLA, também poderia ser responsável pela redução da síntese de triacilgliceróis e, dessa forma, contribuir para a não deposição dos mesmos no adipócito, reduzindo, assim, o seu tamanho 84,119,120 .…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified